Biomechanics of World-Class Men and Women Hurdlers - Hanley, Brian; Walker, Josh; Paradisis, Giorgos P.; Merlino, Stéphane; Bissas, Athanassios (Frontiers in Sports and Active Living, 2021)
The sprint hurdle events require athletes to cross ten hurdles between the start and finish line. The height of the hurdles, and the distances between them, differ for men and women, possibly resulting in technical differences. The aim of this study was to provide a kinematic comparison of in-competition hurdle technique for world-class men and women hurdlers. Video data were collected for the 16 finalists in the 100 m and 110 m hurdles events at the 2017 IAAF World Championships using four high-speed cameras (150 Hz), focusing on the sixth hurdle for the men and fifth for the women. Center of mass (CM) position, joint angles, step lengths and clearance times were compared between sexes at key events before, during and after hurdle clearance. The hurdle height was approximately 7% higher for men when calculated as a proportion of stature (p < 0.001). This discrepancy in relative hurdle height provided women with a kinematic and mechanical advantage over men as they took off farther from the hurdle (relative to hurdle height) (p < 0.001), leading to a lower and more efficient flight parabola. Women were also able to maintain longer relative step lengths after hurdle clearance and showed minimal vertical oscillation of the CM in the stance phases before and after the hurdle compared with men. The lower relative hurdle heights in the women’s event provide a less demanding task, and thus these findings present preliminary evidence to those coaches who advocate revising the women’s hurdle heights in competition.